SAT0329 Lesinurad, A Novel Selective Uric Acid Reabsorption Inhibitor, in Combination with Febuxostat, in Patients with Tophaceous Gout: the Crystal Phase III Clinical Trial. (9th June 2015) - Dalbeth, N.; Jones, G.; Terkeltaub, R.; Khanna, D.; Kopicko, J.; Bhakta, N.; Fung, M.; Storgard, C.; Baumgartner, S.; Perez-Ruiz, F.
Abstract : Background: Lesinurad (LESU; RDEA594) is a selective uric acid reabsorption inhibitor (SURI) being investigated for the treatment of gout in combination with a xanthine oxidase inhibitor. Objectives: The CRYSTAL study is a multinational, randomized, double-blind, placebo-controlled, phase III clinical trial of LESU in combination with febuxostat (FBX) to determine efficacy and safety of combination therapy compared with FBX monotherapy in patients with tophaceous gout (NCT01510769 ). Methods: Patients with gout, ages 18-85 yrs, with serum uric acid (sUA) ≥8 mg/dL (≥6 mg/dL on urate lowering therapy) and ≥1 tophus were given FBX 80 mg qd for 3 weeks before randomization to LESU (200 mg or 400 mg oral, qd) in combination with FBX or placebo (PBO) + FBX. Primary endpoint was proportion of patients with sUA <5.0 mg/dL by Month 6. Secondary endpoints included proportion of patients with complete resolution of ≥1 tophus and percent reduction in tophus area by Month 12. Safety assessments included adverse events and laboratory data. Results: Patients (N=324) were white (79.9%) and male (95.4%) with mean ± SD age of 54.1±11.0 yrs and 14.7±10.9 yrs since gout diagnosis. sUA was 8.7±1.6 mg/dL at screening and 5.3±1.6 mg/dL on FBX at randomization (28% with sUA ≥6 mg/dL). More patients achieved sUA levels <6, <5 (primary endpoint), <4, and <3 mg/dL with LESU+FBX (Figure ). Percentage of patients with complete resolution of ≥1 tophus by Month 12 was 21.1%, 25.5% and 30.3% for FBX+PBO, FBX+LESU200 and FBX+LESU400, respectively. Percent decrease in tophus area by Month 12 was 55.8% and 57.9% for FBX+LESU200 and FBX+LESU400, respectively, vs. 31.3% for FBX + PBO (both p<0.05). Safety data are reported in the Table. More serum creatinine (sCr) increases were observed with LESU+FBX; most resolved at last study visit (Table ). Kidney stones were lower with LESU. Conclusions: In patients with tophaceous gout, LESU (200 or 400 mg) in combination with FBX increased the proportion of patients achieving sUA <5 mg/dL at 6 months compared with FBX alone. LESU in combination with FBX resulted in greater tophus area resolution compared with FBX alone, as well as a dose-ordered numerical increase in the proportion of subjects having complete tophi resolution. LESU was generally well tolerated, except for higher incidence of predominately reversible sCr elevations. Combination therapy with LESU+FBX may represent a future treatment option for patients with tophaceous gout on FBX who warrant additional therapy. Acknowledgements: Research sponsored by Ardea Biosciences/AstraZeneca. Editorial support was provided by PAREXEL and funded by AstraZeneca. Disclosure of Interest: N. Dalbeth Grant/research support from: AstraZeneca, Fonterra, Novartis, Speakers bureau: Savient, Menarini, Novartis, Takeda, and Advisory Boards for AstraZeneca, Fonterra, Takeda, Metabolex, G. Jones Grant/research support from: Abbvie, Ardea, Novartis, Auxilium, Consultant for: Pfizer, Roche, Hospira and Janssen, Speakers bureau: UCB, Roche, Janssen, Abbvie, Novartis, Mundipharma, Amgen, BMS, Pfizer, R. Terkeltaub Consultant for: AstraZeneca, Takeda, Revive, Relburn, UCB, D. Khanna Grant/research support from: AstraZeneca, Consultant for: AstraZeneca, Takeda, J. Kopicko Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca group, N. Bhakta Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca group, M. Fung Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca group, C. Storgard Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca group, S. Baumgartner Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca group, F. Perez-Ruiz Grant/research support from: Spanish Health Ministry, Spanish Rheumatology Foundation, and Cruces Hospital Rheumatologists Association, Consultant for: AstraZeneca, Menarini, Metabolex, Novartis, Pfizer, and SOBI, Speakers bureau: AstraZeneca and Menarini